Digital Melting Curve Analysis for Multiplex Quantification of Nucleic Acids on Droplet Digital PCR - Xiaoqing Dai; Meng Cao; Zunliang Wang (Biosensors)
We present a cost-effective and simple multiplex nucleic acid quantification method using droplet digital PCR (ddPCR) with digital melting curve analysis (MCA). This approach eliminates the need for complex fluorescent probe design, reducing both costs and dependence on fluorescence channels. We developed a convolutional neighborhood search algorithm to correct droplet displacement during heating, ensuring precise tracking and accurate extraction of melting curves. An experimental protocol for digital MCA on the ddPCR platform was established, enabling accurate quantification of six target pathogen genes using a single fluorescence channel, with an average accuracy of 85%. Our method overcomes the multiplexing limitations of ddPCR, facilitating its application in multi-target pathogen detection.